Factores que influyen en la intención de emprendimiento del emprendedor híbrido - Gonzales Peralta, Patricia (2021)
From the theory of planned behavior, factors are proposed that would influence the intention of entrepreneurship in the second stage of hybrid entrepreneurship. This conceptual research makes use of secondary information for thematic analysis of the literature. In this way, a conceptual model and propositions are established. As a result, four factors that influence this intention are determined: The expectation of business growth, entrepreneurial social capital, organizational commitment with the employer and entrepreneurial self-efficacy. Finally, the study has three contributions. First, it offers a multidisciplinary approach by applying the theory in a new context; second, it offers propositions related to the hypotheses of a new conceptual model for subsequent empirical evaluation; and, third, it promotes the visibility of the hybrid entrepreneur in the public policy literature in support of entrepreneurship.